Public, Poor, and Promiscuous? Defining the Prostitute in Sixteenth-Century Zurich - Schulz, Adrina (Religions, 2025)
The impact of the Reformations, in Switzerland and elsewhere, on the regulation of sexuality has been extensively researched in recent decades. Laws against adultery and premarital fornication were strengthened and promulgated, leading to the decline of the late-medieval public brothel. However, the impact of these theological, legal, and institutional changes on the women who engaged in transactional or commercial sex outside of marriage has been harder to capture. Even the authorities’ definitions of such women remain difficult to pin down: were they viewed as promiscuous sinners to be punished, laborers in a dishonorable profession, poor vagrants to be exiled, or all or none of the above? This paper first discusses the historiography of prostitution to show how previous research terminology and definitions of the phenomenon are insufficient for the early modern context. It then analyses a case study from sixteenth-century Zurich in which different understandings about premodern prostitutes coexisted, intersected, and conflicted with the argument that these individuals were conceived of in terms of authorities’ fears rather than a specific set of characteristics.